2019
DOI: 10.1016/j.invent.2019.100281
|View full text |Cite
|
Sign up to set email alerts
|

Using stepped-care approaches within internet-based interventions for youth anxiety: Three case studies

Abstract: BackgroundThere are a lack of clear guidelines for the dissemination of Internet-based cognitive behaviour therapy (ICBT) for childhood and adolescent anxiety in routine care. While self-guided ICBT has greater reach than therapist-guided ICBT, it is plagued by problems of low program adherence and many young people are not successfully treated. It is important that we identify models of ICBT that are accessible, but provide the right support, at the right time to those who need it. Stepped-care models of ICBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…HAS participants could be easily identified at the beginning of the program (due to higher initial scores), and subsequently referred, monitored, and provided with additional support or intervention elements if their response to the program was poor. Preliminary results from case studies of a stepped-care model of BRAVE highlight the potential of this approach [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…HAS participants could be easily identified at the beginning of the program (due to higher initial scores), and subsequently referred, monitored, and provided with additional support or intervention elements if their response to the program was poor. Preliminary results from case studies of a stepped-care model of BRAVE highlight the potential of this approach [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies showed favorable results for these interventions' use (Calear et al, 2009;Chillemi et al, 2020;Hill and Pettit, 2016;March et al, 2019;Perry et al, 2017;Rapoff et al, 2014;Rees et al, 2016;Saulsberry et al, 2013;Wade et al, 2019). Despite this, it is concerning how much the number of interventions found in this study contrasts with the number and pace at which e-Health apps are being released in app stores (Olff, 2015).…”
Section: Types Of Studies and Interventionsmentioning
confidence: 73%
“…The 19 articles describe the 13 interventions through: seven efficacy studies with at least two groups (Calear et al, 2009;Hetrick et al, 2017;O'Kearney et al, 2006;Perry et al, 2017;Rapoff et al, 2014;Saulsberry et al, 2013;Van Voorhees et al, 2009), five efficacy studies protocols (Baldwin et al, 2021;Gladstone et al, 2015;Hides et al, 2020;Palermo et al, 2018;Rees et al, 2015), four pilot or preliminary data studies (Chillemi et al, 2020;Hill e Pettit, 2016;Rees et al, 2016;Wade et al, 2019), two complementary aspects studies -such as lessons learned and adherence (Anderson et al, 2017;Calear et al, 2013), and three case studies (March et al, 2019). Interventions and their main characteristics are described in Table 1.…”
Section: Types Of Studies and Interventionsmentioning
confidence: 99%
“…Third, they are able to deliver a service experience that is tailored to the needs and preferences of each individual young person through personalization [ 21 ]. Finally, there are many evidence-based digital mental health services that can be accessed for free or at a low cost, with no waiting period [ 22 , 23 ]. Digital services might also act as an alternative or adjunct intervention when young people have had previous negative experiences with mental health professionals.…”
Section: Introductionmentioning
confidence: 99%